Keanekaragaman Tumbuhan Pakan dan Perilaku Monyet Ekor Panjang (Macaca fascicularis) di Kawasan Cagar Alam Wolo Tadho (Studi Kasus Di Desa Tadho, Kecamatan Riung, Kabupaten Ngada) - Fernanda Solagracia Nauk; Maria M. E. Purnama; Fadlan Pramatana (Wana Lestari, 2024)
This research was conducted in Tadho Village, Wolo Tadho Nature Reserve Area, Riung District, Ngada Regency, East Nusa Tenggara Province, from July to August 2023. This study aims to identify the types of plants that have the potential as a source of food. Knowing the behavior of Long-tailed Monkeys in the Wolo Tadho Nature Reserve Area. The method used in this study was the Focal animal sampling method, where observations of animal movements began in 3 periods, namely (a) period I (07.00 to 09.00 WITA), (b) period II (11.00 to 13.00 WITA) and (c) period III (15.00 to 17.00 WITA) with a time interval of 10 minutes. Observations were conducted on one individual Long-tailed Macaque (Macaca fascicularis) and its behavior was followed and recorded using One Zero Sampling. One Zero Sampling is the recording of the dominant behavior within the time interval of an observation session. The results of the study found the number of plants that have the potential as a food source in the Wolo Tadho Nature Reserve area there are 15 types of plants known to be selected by long-tailed monkeys (Macaca fascicularis) as food. The most dominant vegetation types are Lamtoro (Leucaena leucocephala), Tamarind (Tamarindus indica L) and Mangrove (Rhizophora apiculata) and the daily behavior of long-tailed monkeys (Macaca fascicularis) which is often done is moving 31%. Many behaviors were Feeding 19%, Resting 16%, Grooming 15%, Foraging 8% Playing 9%. Rare behaviors were Agression 1% and Mating 1%. While the behavior that was not seen was Object Play 0%.